Pathogenic mechanisms and potential applications of extracellular vesicles from periodontal pathogens in periodontitis - Zhang, Ruiqing; Li, Guoliang; Wu, Yingtao; Wang, Xiaoxuan; Luan, Qingxian (Frontiers in Immunology, 2024)
Periodontitis is a multifactorial disease characterized by chronic destruction of the periodontal supporting tissues and is closely associated with the dysbiosis of the plaque biofilm. It is the leading cause of tooth loss in adults. Bacterial extracellular vesicles (BEVs) are released from bacteria, which range in size from 20 to 400 nm. These vesicles contain various components derived from their parent bacteria, including nucleic acids, proteins, lipids, and other molecules, which facilitate functions such as molecular transfer, metabolic regulation, bacterial interactions, biofilm formation, and immune modulation. BEVs participated in the pathophysiological process of periodontitis. Recently emerging evidence also showed that the contents of EVs in saliva and gingival crevicular fluid (miRNAs, mRNAs, and proteins) could be used as potential biomarkers for periodontitis. While most current research focuses on human-derived components, much less is known about BEVs. Therefore, this review introduces the formation mechanisms and components of BEVs related to periodontitis. Then, this review summarizes the current information about the mechanism, the diagnostic and theraputic value of periodontal pathogen-derived extracellular vesicles in the development of periodontitis. Furthermore, the future challenges of exploring the role of BEVs in periodontitis are also discussed.